Collapse behaviour of a fire engineering designed single-storey cold- formed steel building in severe fires. (September 2019) - Roy, Krishanu; Lim, James B.P.; Lau, Hieng Ho; Yong, P.M.; Clifton, G.C.; Johnston, Ross P.D.; Wrzesien, Andrzej; Mei, Chee Chiang
Abstract: This paper describes a full-scale natural fire test to investigate the collapse behaviour of a single storey cold-formed steel (CFS) building, designed to behave in a specified way in a severe fire, with roof venting and partial wall collapse. The test building had a span of 8 m, height-to-eaves of 2.15 m, and length of 10 m. The walls of the CFS building were constructed from cantilever 'stud & track' panels, with stud spacing of 0.6 m. The roof of the building comprised CFS trusses pinned to the wall connection plates at the top. In this fire test, walls on two adjacent sides were lined internally with fire resistant lining to achieve a structural fire resistance of 30 min (R30) and the calculated fire load was provided to generate a structural fire severity of 30 min, taking into account roof venting. Thus the two protected walls were expected to remain vertical throughout the fire; the roof was expected to collapse first, followed by pulling in of the unprotected walls. The CFS cantilever wall/roof truss system collapsed with an inwards asymmetrical collapse mechanism at a truss temperature of 622.5 °C, with collapse being due to member buckling of the non-fire rated wall rather than failure of the screws or joints. A non-linear finite-element (FE) model is then described. The collapse temperature predicted using the FE was 628.2 °C, with a deformed shape similar to that observed in the fire test. The FE model has matched the experimental behaviour, thus making this model useful in understanding and predicting the behaviour of CFS cantilever wall/truss system in severe fire conditions. Highlights: A full-scale natural fire test on a single-storey building constructed entirely of cold-formed steel (CFS) is described. The walls on two adjacent sides were lined internally with fire resistant lining to achieve a structural fire resistance of 30 min (R30). The CFS cantilever wall/truss system collapsed inward asymmetrically at 622.5 °C and, at a time of 21 min 30 s. A layer of 15 mm gypsum board protected the CFS stud in the South and West walls from 45% rise in temperature and a time delay of 46%. A non-linear finite-element model is described which predicted the failure temparature as 628.2 °C, with a deformed shape similar to the test results.